Deformation, fracture characteristics and damage constitutive model of soft coal under true triaxial complex stress paths - Chongyang Jiang; Lianguo Wang; Jiaxing Guo; Shuai Wang (PLoS ONE, 2025)
Understanding the mechanical properties and damage deterioration mechanisms of soft coal under true triaxial complex stress paths is crucial for predicting and evaluating the stability of the roof during roadway excavation in thick soft coal seams. This study examines the evolution of deformation strength, fracture characteristics, and acoustic emission patterns of soft coal under various initial stress levels and stress paths using true triaxial loading and unloading tests. The research reveals that soft coal undergoes rapid expansion deformation and ultimately fails along the unloading direction, which varies with different stress paths. The initial stress level and stress path significantly influence deformation and strength, conforming to the Mogi-Coulomb criterion. The fracture modes of the coal under different stress paths can be categorized into compressive-shear failure and compression-shear and tension composite failure. Furthermore, based on the experimental results, a damage constitutive model for soft coal is developed that integrates damage mechanics, Weibull statistical distribution theory, and the Mogi-Coulomb criterion to effectively measure microelement strength under true triaxial complex stress paths. Comparing the theoretical model with the experimental curves demonstrates that the proposed damage constitutive model can effectively reflect the deformation strength characteristics of soft coal under true triaxial complex stress paths. These findings offer a crucial theoretical foundation for enhancing methods to predict and evaluate the stability of roadway roofs in soft coal seams, potentially improving safety and efficiency in mining operations.